Cash WAQF as an effective tool of financing MSMEs for sustainable poverty alleviation: a Nigerian perspective - Sanyinna, Abubakar Yusuf; Hashim, Hydzulkifli; Osman, Muhammad Farihal (Islamic Business School, 2018)
Poverty is not only an impediment to any meaningful development but a grazing ground for numerous crimes and civil disobedience. Globally, micro, small and medium enterprises (MSMEs) are generally known to contribute immensely towards poverty alleviation through their employment-generating potentials. In Nigeria, as this paper reveals, these potentials of MSMEs are seriously constrained by a lack of access to finance for the commencement, expansion or modernization of entrepreneurial activities. With the current state of waqf institution in the predominantly Muslim states in the country, this paper presents an operational mechanism for financing MSMEs in a bid to reduce the rate of poverty to the lowest level. The management of cash waqf has numerous debt and equity Islamic financing techniques based on profitand-loss-sharing (PLS) system that could be employed to achieve the desired objective. This paper is composed using a combination of literature review and exploratory approach in qualitative research method.